Loss-of-function mutation of PCSK9 as a protective factor in the clinical expression of familial hypercholesterolemia: A case report. Issue 34 (21st August 2020) - Bayona, Ane; Arrieta, Francisco; Rodríguez-Jiménez, Carmen; Cerrato, Francisco; Rodríguez-Nóvoa, Sonia; Fernández-Lucas, Milagros; Gómez-Coronado, Diego; Mata, Pedro
Abstract: Rationale: Proprotein convertase subtilisin/kexin 9 or PCSK9 is a protein whose main function is to regulate the number of low-density lipoprotein receptors (LDLR) present on the cell surface. Loss-of-function mutations in PCSK9 have been related to low LDL-cholesterol levels and a decrease in the risk of cardiovascular events. Patient concerns: We present the case of a 27-year-old woman, offspring of a patient with familial homozygous hypercholesterolemia, who presented with mild-moderate hypercholesterolemia. Diagnosis: Genetic analysis was performed by next generation sequencing using a customized panel of 198 genes. Sanger sequencing was used to confirm the presence of the variants of interest. The genetic analysis showed a pathogenic heterozygous mutation in LDLR [ exon 6:c.902A>G: p(Asp301Gly)], as well as a loss-of-function heterozygous variant in PCSK9 [ exon1:c.137 G>T: p.(Arg46Leu)]. The genetic analysis of the index case's mother revealed compound heterozygosity for 2 different mutations in LDLR [ c.902A>G: p.(Asp301Gly); c.1646G>T: p.(Gly549Val)] in exon 6 and in exon 11, respectively, and the same loss-of-function variant in PCSK9 that had been found in her daughter [( PCSK9:exon1:c.137G>T: p.(Arg46Leu)]. The maternal grandfather of the index case presented the same genetic variants as his granddaughter. Interventions: The index case did not receive any specific treatment for hypercholesterolemia. The loss-of-function variant in PCSK9 protected her from higher LDL-cholesterol levels, provided she kept partial activity of the LDLR. In her mother, instead, a PCSK9 inhibitor was tried but failed to achieve lipid control. The reason for this may be the complete absence in LDL receptor activity. LDL apheresis was started afterwards, resulting in adequate lipid level control. Outcomes: To the date, the index case has achieved to maintain adequate total and LDL-cholesterol levels without any other intervention. She has had no known cardiovascular complication. Lessons: Loss-of-function mutations in PCSK9 could protect from developing more severe forms of hypercholesterolemia. The finding of these mutations ( LDLR-PCSK9 ) in three consecutive generations could imply an adaptive mechanism against the development of hypercholesterolemia.